2015
DOI: 10.3174/ajnr.a4519
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal Brain Laceration as a Predictor of Abusive Head Trauma

Abstract: BACKGROUND AND PURPOSE:Accurate differentiation of abusive head trauma and accidental head injury in infants and young children is critical and impacts clinical care, patient prognosis, forensic investigations, and medicolegal proceedings. No specific finding seen on cross-sectional brain imaging has been reported to distinguish abusive head trauma from accidental injury. Our study investigated whether a specific imaging finding, parenchymal brain laceration, is unique to children diagnosed with abusive head t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 15 publications
(25 reference statements)
0
16
0
4
Order By: Relevance
“…35 Palifka et al demonstrated parenchymal laceration in 13% (18/137) of cases of AHT, while none were detected in patients with accidental trauma, suggesting parenchymal laceration may also be indicative of AHT. 36 CT only detected half (9/18) of the cases of parenchymal laceration seen on MR, illustrating the importance of MRI in detecting this injury. An older study by Calder et al further demonstrated that contusional tears were present in a group of nine infants under the age of 5 months who died from repeated AHT.…”
Section: Conventionalmentioning
confidence: 97%
“…35 Palifka et al demonstrated parenchymal laceration in 13% (18/137) of cases of AHT, while none were detected in patients with accidental trauma, suggesting parenchymal laceration may also be indicative of AHT. 36 CT only detected half (9/18) of the cases of parenchymal laceration seen on MR, illustrating the importance of MRI in detecting this injury. An older study by Calder et al further demonstrated that contusional tears were present in a group of nine infants under the age of 5 months who died from repeated AHT.…”
Section: Conventionalmentioning
confidence: 97%
“…This certainty is higher for children with more severe presentations or with multiple findings [17,41]. Several characteristic findings have, most frequently, been identified in AHT including subdural hematoma (SDH), brain parenchymal injuries, retinal hemorrhages and rib fractures [2,10,41,42]. In the review by Maguire et al [41], any combination of 3 or more of the significant diagnostic features yielded a positive predictive value of 85%.…”
Section: What Are the Presenting Features Of Aht?mentioning
confidence: 99%
“…Cerebral white matter (WM) lacerations associated with head trauma have been reported in infants less than 1 year [1,2]. WM lacerations are observed in the unmyelinated WM in early infancy, while patients older than 1 year show traumatic WM injury that is very similar to that observed in adults, such as diffuse axonal injury, callosal injury, and parenchymal hemorrhage [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that the poorly myelinated infantile WM with a gelatin-like consistency, the very pliant skull with non-fused sutures, and the shallowness of the subarachnoid space predispose to parenchymal lacerations in the context of shear force generated from trauma [2,5]. WM lacerations have only been observed in young infants with abusive head trauma (AHT), i.e., never with accidental head injury, leading to the concept that WM lacerations may represent a pattern of injury unique to AHT [1]. We first report three teenagers with severe WM lacerations which could be associated with repetitive impacts to their heads.…”
Section: Introductionmentioning
confidence: 99%